Salivary and serum levels of neutrophil proteases in periodontitis and rheumatoid arthritis - Yilmaz Dogukan; Niskanen Katariina; Gonullu Emel; Tervahartiala Taina; Gursoy Ulvi K; Sorsa Timo (WILEY, 2025)
Objective: The aim was to profile serum and salivary levels of active-matrix metalloproteinase (aMMP)-8, tissue inhibitor MMP (TIMP)-1, aMMP-8/TIMP-1 ratio, total MMP (tMMP)-9, tMMP-9/TIMP-1 ratio, myeloperoxidase (MPO), and human neutrophil elastase (HNE) in periodontitis and rheumatoid arthritis (RA).Materials and Methods: Rheumatoid arthritis patients with periodontitis (RA + P, n = 26), periodontally healthy RA patients (RA, n = 23), systemically healthy periodontitis patients (P, n = 24), and controls (C, n = 24) were included. aMMP-8 levels were determined by a time-resolved immunofluorescence assay (IFMA), TIMP-1, tMMP-9, MPO, and HNE levels were measured by enzyme-linked immunosorbent (ELISA) assays.Results: Higher salivary aMMP-8 (p < 0.001), aMMP-8/TIMP-1 ratio (p = 0.043), tMMP-9 (p = 0.011), tMMP-9/TIMP-1 ratio (p = 0.022), MPO (p = 0.026) and HNE (p < 0.001) levels were detected in P relative to the controls. Salivary TIMP-1 was increased in RA patients regardless of periodontal status (RA + P vs. P: p = 0.038; RA vs. C: p = 0.020). Serum neutrophil proteases were increased in RA groups (RA + P, RA) compared to systemically healthy groups (P, C) (p < 0.05).Conclusions: Serum levels of neutrophil proteases were increased in RA study groups; however rheumatologic status seemingly does not affect salivary levels of these proteins.